Turgenev Today: On the Problem of Perception - Belyaeva, Irina (Slavica, 2018)
The article deals with the question of how Turgenev’s work is perceived by the modern reader. There are identified aspects related to the complexity of understanding the writer’s texts, which are largely due to stereotypes that have developed in the culture of perception, and are also features of his poetics. There are different ways of new interpretations of Turgenev’s famous texts – those of the novels “Fathers and Sons” and “The Noble Nest”. In “Fathers and Sons” the idea of reconciliation with contradictions is emphasized, and ‘The Noble’s Nest” is considered a successful social project in literature. The article briefly highlights the main stages of Turgenev’s popularizing Russian culture in the West.